Factors characterizing access and latency to first pharmacological treatment in Italian patients with schizophrenia, mood, and anxiety spectrum disorders. (January 2015) - Dell'Osso, Bernardo; Cremaschi, Laura; Palazzo, Carlotta; Suardi, Neva; Spagnolin, Gregorio; Camuri, Giulia; Benatti, Beatrice; Oldani, Lucio; Dobrea, Cristina; Arici, Chiara; Pace, Giovanna; Tiseo, Alessandra; et al.
Abstract : Latency to first pharmacological treatment [duration of untreated illness (DUI)] in psychiatric disorders can be measured in years, with differences across diagnostic areas and relevant consequences in terms of socio-occupational functioning and outcome. Within the psychopathological onset of a specific disorder, many factors influence access and latency to first pharmacotherapy and the present study aimed to investigate such factors, through an ad-hoc developed questionnaire, in a sample of 538 patients with diagnoses of schizophrenia-spectrum disorder (SZ), mood disorder (MD), and anxiety disorder (AD). Patients with SZs showed earlier ages at onset, first diagnosis and treatment, as well as shorter DUI compared with other patients (43.17 months vs. 58.64 and 80.43 months in MD and AD; F =3.813, P =0.02). Patients with MD and AD reported more frequently onset-related stressful events, benzodiazepines as first treatment, and autonomous help seeking compared with patients with SZs. In terms of first therapist, psychiatrist referral accounted for 43.6% of the cases, progressively decreasing from SZ to MD and AD (57.6, 41.8, and 38.3%, respectively). The opposite phenomenon was observed for nonpsychiatrist clinician referrals, whereas psychologist referrals remained constant. The present findings confirm the presence of a relevant DUI in a large sample of Italian patients with different psychiatric disorders (5 years, on average), pointing out specific differences, in terms of treatment access and latency, between psychotic and affective patients. Such aspects are relevant for detection of at-risk patients and implement early intervention programs.